Moderasi Beragama : Analisis Kebijakan dan Strategi Penguatan di Kementerian Agama Republik Indonesia - Rofiqi Rofiqi; Mohammad Firdaus; Mohamad Salik; Achmad Zaini (Ulumuna: Jurnal Studi Keilsman, 2023)
Religious moderation is currently a very interesting discussion, not only among academics but also among the public. The emergence of the phenomenon of intolerance and radicalism certainly becomes asbabun nuzul from moderation so the Ministry of Religion of the Republic of Indonesia feels the need to make religious moderation a policy focus. This paper aims to reveal policy analysis and strategies for strengthening religious moderation in the context of education in Indonesia. The research method used is qualitative with the type of library research using the note-taking technique. The results of this study indicate that the policy of strengthening religious moderation is contained in the 2020-2024 RPJMN which promotes strengthening religious moderation through 5 (five) strategies to strengthen religious moderation including; religious broadcasting, education system, management of houses of worship, management of public spaces, and Islamic boarding schools. However, the focus and findings in this study lead to the implementation of the education system in Islamic Higher Education, in which houses of religious moderation are formed at State Islamic Universities in Indonesia.